A Common Force-Sharing Pattern in Joint Action That Consists of Four People. Issue 1 (2nd January 2019) - Masumoto, Junya; Inui, Nobuyuki
ABSTRACT: The authors examined the force-sharing patterns in a joint action performed by a group of two, three, or four people compared with a solo action. In the joint actions, 28 participants produced periodic isometric forces such that the sum of forces they produced cycled between 5% and 10% maximum voluntary contraction with the right hand at 1 Hz. In both the three- and four-person tasks, the correlation between forces produced by two of the three or four participants was negative, and the remaining one or two participants produced intermediate forces. The errors of force and interval and force variabilities were smaller in four- and three-people groups than individuals. Four- and three-people groups thus performed better than individuals.